"Brain steatosis" in an obese mouse model during cycles of Famine and Feast the underestimated role of fat (WAT) in brain volume formation. Issue 3 (2017) - Ginneken, Vincent van; Vries, Evert de; Verheij, Elwin; Greef, Jan van der
No abstract available